A New Pollen Preparation Technique Using Technical Chemicals - Sukapti, Woro Sri; Yulianto, Eko (Geological Agency, 2024)
The widespread use of pollen analysis in various fields in Indonesia is hampered mainly by the application of pro-analyst chemicals in standard pollen preparation. To solve this problem, a new pollen preparation technique using technical chemicals was developed. The results of comparison between this new technique with the standard technique used before showed that the pollen-spore yields, the quality of pollen slides, and the slide visibility resulted from both techniques is comparable. Furthermore, the new technique reduced the chemical cost of the standard technique by IDR. 87,125.00 per sample.